Identification of monoclinic θ-phase dispersoids in a 6061 aluminium alloy. (2nd April 2016) - Buchanan, Karl; Ribis, Joël; Garnier, Jérôme; Colas, Kimberly
Abstract: Intermetallic dispersoids play an important role in controlling the 6xxx alloy series' grain distribution and increasing the alloy's toughness. The dispersoid distribution in a 6061 aluminium alloy (Al–Mg–Si) was analysed by transmission electron microscopy, selected area diffraction and energy-dispersive X-ray spectroscopy. The dispersoids had three unique crystal structures: simple cubic, body-centred cubic and monoclinic ( C 2 /m ). While the SC and BCC dispersoids have been well characterized in the literature, a detailed analysis of monoclinic dispersoids has not been presented. Therefore, the current work discusses the chemical composition, crystal structure and morphology of the monoclinic dispersoids.